EPIDEMIOLOGICAL PROFILE AND GLOBAL DEVELOPMENT OF CHILDREN FROM 0 TO 5 YEARS OF AGE IN A DISTRICT IN THE INTERIOR OF BAHIA - da Silva Araújo, Cintia; Nayelle Ferreira de Sousa, Sara; Cortiana Rodrigues Lima, Sabrine; Maia Souza, Clevane; dos Santos Amorim, Mayara (Health and Society, 2022)
Introduction: Early childhood corresponds to the period from birth to 6 years of age, it is during this period that the child gains fundamental skills for the full development of various skills. However, many factors can influence this development, such as physical, family and social issues, social isolation, for example, caused a process of transformation of the domestic environment, which started to add a set of activities related to work, school and even even physical activity. The current context of the pandemic has generated impacts on education, family life, economic and global development of children, because with isolation, many activities were restricted, as well as the functioning of daycare centers and schools, which often played a fundamental role. in the nutrition of some children. Objective: To profile the global development of children aged 0 to 5 years in a district in the interior of Bahia. Materials and methods: The research was carried out in Capoeiruçu, district of Cachoeira-Ba, and children from 0 to 5 years old living in the district were included in the study. epidemiological; Ages & Stages Questionaires -3, and the Early Childhood Development Index 2030. The collected data were tabulated in a database in the Statistical Software Package for the Social Sciences (SPSS) version 22. Results: According to the analysis, about 47.20% of families survive with 2 or less minimum wages per month and 32.4% of parents have completed high school. In addition, 55.9% of mothers had health problems during pregnancy, such as anemia and hypertension. Another impacting factor is that 41.20% of these parents and caregivers were unemployed in the pandemic, reporting that 64.7% of these families were infected with the COVID-19 virus. Of the total number of families interviewed, 55.9% reported that their children became more dependent on activities such as playing, running or anything else. Conclusion: According to the results presented, we can point out that, although some of these children have some factors that may influence a deficit in global development, they still had a good income, as these qualities may be linked to the fact that the community is composed mainly by university students in the health area, which favors obtaining more information on issues related to the typical development of children.